Analysis of intraoperative frozen section consultations and audit of accuracy: a two year experience in a tertiary care multispeciality hospital in India - Maurya, Vinay P.; Rana, Vandana; Kulhari, Kanchan; Kumar, Prashant; Takkar, Puneet; Singh, Nitu (International Journal of Research in Medical Sciences, 2020)
Background: Diagnostic accuracy of intra-operative frozen section (FS) depends largely on quality of tissue sections backed by good clinical communication and experience of reporting pathologist. Periodic audit of this consultation in surgical pathology help in assessing the efficiency of procedure and addressing the pitfalls. In this study authors have analysed the spectrum, indications and assessed the accuracy of FS consultation in their institution. Methods: A retrospective study of 212 consequent tissue specimens submitted for FS over two years in study centre was conducted. The FS and corresponding formalin fixed paraffin embedded (FFPE) tissue section with their final histopathological examination (HPE) reports were studied and analyzed. The results were classified in concordant, discordant and deferred categories. Accuracy rates and discordant frequencies were calculated and comparison with other similar studies was done. Reasons for inaccuracies were deduced. Results: A total of 212 tissue specimens for FS were reported over two years in this study institute, six of which showed discordant results. Most common site of FS in this study centre was from central nervous system (CNS) lesions (28.77%). Indications for intra-operative consultation were mainly for establishment of tumor diagnosis (66.51%) and status of margins (29.25%). The accuracy rate was found to be 97.17% with error rate of 2.83%. On analysis of discordant cases; the reason for inaccuracy was mainly due to interpretation error (83.33%). Conclusions: The audit of FS consultation established that accuracy rates of this study institution are comparable with most international quality control statistics for FS. The discordant cases were mostly false positive hence emphasising that a variable degree of reservation is required while interpreting and communicating the FS results. The closest possible diagnosis should be communicated on FS and definitive diagnosis should be deferred to HPE in case of doubt.